Effectiveness of Self-Contained Breathing Apparatus: An Observational Study on Exposure to Polycyclic Aromatic Hydrocarbons and Associated Respiratory Risks - Joana Teixeira; Cristina Delerue-Matos; Alice Santos-Silva; Francisca Rodrigues; Marta Oliveira (Fire)
Background: An effective risk assessment and management methodology is essential to minimize/mitigate health risks associated with firefighting activities. The use of a self-contained breathing apparatus (SCBA) is mandatory during structure fires to protect firefighters from hazardous fire effluents, yet the protectiveness of the SCBA system has rarely been evaluated. Objective: This study characterizes, for the first time, the levels of 18 polycyclic aromatic hydrocarbons (PAHs) inside the SCBA facemask, during 7 structure-firefighting exercises and estimates associated respiratory risks. Methods: Cotton disk samples were collected via passive air sampling and analyzed using liquid chromatography with fluorescence and UV–Vis detection. Results: Levels of total PAHs (∑PAHs: 9.17–29.6 ng/m3) and ∑PAHscarcinogenic (0.41–5.73 ng/m3) were below the occupational limits defined by governmental agencies. The low-molecular-weight PAHs were predominant (79.5–91.4%), and the (possible/known) carcinogenic naphthalene (0.26–2.00 ng/m3), anthracene (0.088–0.31 ng/m3), chrysene (0.046–0.39 ng/m3), benzo(b+j)fluoranthene (0.18–0.40 ng/m3), and benzo(a)pyrene (0.041–0.18 ng/m3) were detected in all samples. The respiratory health risk analysis demonstrated negligible risks associated with the inhalation of PAHs. A health principal component analysis could identify firefighters at increased respiratory risk. Conclusions: The effectiveness of SCBA was demonstrated, reinforcing the need to ensure its correct use during all the phases of structure fires, including during overhaul.